# Write in slope-intercept form with the given information

Answer: you have to use point slope form

point slope form: y - y1 = m(x - x1)

x1 and y1 are the x and y values of the given point

m is the slope

so, just plug in the numbers:

y-3 = -2(x + 8)

now solve to put into slope intercept form (y = mx + b)

y-3 = -2x - 16

y=-2x-13

Step-by-step explanation:

I am not sure if these what they want.

y-b=m(x-a)

y-3=-2(x--8)

y-3=-2x-16

y=-2x-13

## Related Questions

how many years (to two decimal places) will it take an investment of $17,000 to grow to$41,000 if it is invested at 2.95% compounded continuously

30 years

Step-by-step explanation:

Given data

P=$17,000 A=$41,000

R=2.95%

the expressio for the time is

t= ln(A/P)/r

t= ln(41,000 /17000)/0.0295

t= ln(2.41176)/0.0295

t= 0.8803/0.0295

t= 29.8

What is the product? 2x+8 x2 + 3x-4 x(x-4)(x-1) 20x+4) 2 (x+4)(x-4) 2x(x-1) 2x(x+4)​

The products of the given expressions are:

Here, we have to find the product of the expressions given,

let's multiply them step by step:

First, apply the distributive property:

Product of (2x + 8) and

Combine like terms:

Product =

Product =

(x - 4)(x - 1)(20x + 4):

First, apply the distributive property:

Now, multiply the result with (20x + 4):

Combine like terms:

Product =

Product =

2(x + 4)(x - 4):

First, apply the distributive property:

2(x + 4) = 2x + 8

Now, multiply the result with (x - 4):

Combine like terms:

Product =

Product =

2x(x - 1):

Apply the distributive property:

2x * (-1) = -2x

Combine the terms:

Product =

2x(x + 4):

Apply the distributive property:

2x * 4 = 8x

Combine the terms:

Product =

So, the products of the given expressions are:

brainly.com/question/5992872

#SPJ5

=−640x10+1280x9+19904x8−40728x7−144488x6+323904x5−162304x4+1024x3+2048x2

step by step

(2x+8x2+3x−4x(x−4)(x−1)(20)x+4)(2)(x+4)(x−4)(2)x(x−1)(2)x(x+4)

=((2x+8x2+3x−4x(x−4)(x−1)(20)x+4)(2)(x+4)(x−4)(2)x(x−1)(2)x)(x+4)

=((2x+8x2+3x−4x(x−4)(x−1)(20)x+4)(2)(x+4)(x−4)(2)x(x−1)(2)x)(x)+((2x+8x2+3x−4x(x−4)(x−1)(20)x+4)(2)(x+4)(x−4)(2)x(x−1)(2)x)(4)

=−640x10+3840x9+4544x8−58904x7+91128x6−40608x5+128x4+512x3−2560x9+15360x8+18176x7−235616x6+364512x5−162432x4+512x3+2048x2

=−640x10+1280x9+19904x8−40728x7−144488x6+323904x5−162304x4+1024x3+2048x2

A rectangular. Garden bed measures 8 x 6 feet a water faucet is at one corner of the bed hose must be long enough to reach opposite corner when stretched straight. Find required length of hose

10 ft

Step-by-step explanation:

The word problem is basically asking the length of one corner of the rectangle to the other. We can split the rectangle up into two right triangles and we will use the Pythagorean theorem to find the hypotenuse or the length from one corner to another. A^2 + B^2 = C^2 A and B are the lengths of the rectangle, 8 and 6. 8^2 + 6^2 = C^2

8^2 = 64 and 6^2 = 36

64 + 36 = 100.

the square root of 100 is 10 so the length of the hose is `10.

What's the square root of 25, 100, 36, 84, and 4.

Step-by-step explanation:

The product of two numbers is 16/3 if one of the number is 48/5 what is the other one?

The other number is 5/9.

Step-by-step explanation:

16/3 = 48/5 * x

x = 5/9

x = 20

<ACD = 113

Step-by-step explanation:

Exterior angle of a triangle is equal to the sum of the interior opposite angles of a triangle

There for,

<CAB + <ABC = <ACD

Size of the <ACD